NEW CIS UNIVERSITY LEAGUE TABLES - CORRELATIONS WITH THE WEBOMETRICS RANKINGS - Sergey V. Ablameyko; Michail A. Zhuravkov; Viktor V. Samokhval; Lyudmila M. Khukhlyndina (Moscow Polytechnic University, 2016)
The outcomes of the Webometrics ranking, published by the Spanish National Research Council in 2014 are correlated against the new regional university rankings compiled by the Russian agencies Interfax and Expert-RA. It is shown that coverage by the regional rankings can be increased by grouping the participating universities according to profile. The quantitative indicators are shown for higher education institutions worldwide and separately for the CIS HEIs occupying the first 100 places in the 2013 and 2014 rankings.